Ucwaningo olunzulu ngesu lokusetshenziswa kwesathaya emculweni kaMaskandi nomthelela ekuphilisaneni kwabantu - Khumalo, Dumisani Ephraim (My University, 2022)
Maskandi music is a form of art that has unique features which make it stand out from the other forms of music genre. Its close contact with people's lives, way of life, and its ability to express ideas about issues that society is reluctant to address make this type of music genre assume a big part of how African people, especially the lowly and neglected present how they feel. An in-depth study of the use of satire in maskandi music and the impacts on social cohesion further investigates the relationship between the art of satire with maskandi music genre. It also comments on various implications of the use of satire as part of maskandi music. This study focused on the exploration of information from various maskandi artists' reasons for using satire and the effects achieved in different societies. The research uses the qualitative approach to conduct interviews and listen to a variety of songs, as well as search for information and ideas on the topic under investigation. Hermeneutics philosophy and semiotics as its subsequent theory were used to analyze information on ideas presented through satire in maskandi songs. The study also employed Communication Accommodation Theory (CAT) to analyze people’s comments on the effects of satire on maskandi music. The results of this study identified various reasons for the use of satire in maskandi music including, maskandi artists making a name for themselves, expressing heroism through artists, and ensuring the popularity and marketing of their music. This study also acquired new insights into how maskandi music, through the use of satire, contributed to the emergence of new terminology in the language, the transformation of attitudes, and the promotion of trade and business opportunities.
A thesis submitted in fulfilment of the requirement for the degree Doctor of Philosophy (PhD) to the Faculty of Humanities in African Languages and Linguistics, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2022